2009
DOI: 10.1158/0008-5472.can-08-3643
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Suppresses Squamous Carcinogenic Progression and Epithelial-Mesenchymal Transition

Abstract: Hypoxia-inducible factor-1 is a known cancer progression factor, promoting growth, spread, and metastasis. However, in selected contexts HIF-1 is a tumor suppressor coordinating hypoxic cell cycle suppression and apoptosis. Prior studies focused on HIF-1 function in established malignancy, however little is known about its role during the entire process of carcinogenesis from neoplasia induction to malignancy. Here we tested HIF-1 gain of function during multistage murine skin chemical carcinogenesis in K14-HI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 45 publications
3
46
1
1
Order By: Relevance
“…The expression of HIF-1a was increased by hydrogen peroxide treatment, as shown by the control groups (SMMC7721 and SMMC7721-Mock), and an increase in SBP1 expressions could also be observed in the same groups. This is consistent with the finding that SBP1 is a target gene for HIF-1a (20). However, in the SMMC7721 groups where SBP1 expression was downregulated by siRNA treatment, the expression of HIF-1a was not elevated by hydrogen peroxide treatment.…”
Section: Sbp1 Inhibits Proliferation and Induces Apoptosis Only Aftersupporting
confidence: 91%
See 2 more Smart Citations
“…The expression of HIF-1a was increased by hydrogen peroxide treatment, as shown by the control groups (SMMC7721 and SMMC7721-Mock), and an increase in SBP1 expressions could also be observed in the same groups. This is consistent with the finding that SBP1 is a target gene for HIF-1a (20). However, in the SMMC7721 groups where SBP1 expression was downregulated by siRNA treatment, the expression of HIF-1a was not elevated by hydrogen peroxide treatment.…”
Section: Sbp1 Inhibits Proliferation and Induces Apoptosis Only Aftersupporting
confidence: 91%
“…ROS could initiate the activation of HIF-1a (21), whereas HIF-1a could regulate the expression of SBP1 through a hypoxia response element in its promoter region (20). On the basis of this effect, ROS would elevate the expression of SBP1 through HIF-1a mediation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that in murine keratinocytes HIF-1α may arrest cell proliferation (14). Because HIF-1α is inducible by hypoxia, a component of ischemia (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of HIF-1α has been detected in >70% of solid tumors. While upregulation or activation of HIF-1α promotes tumor growth, downregulation or loss of HIF-1α activity has been demonstrated to markedly decrease tumor growth, vascularization and energy metabolism (8)(9)(10)(11). The suppression of HIF-1α expression by RNA interference (RNAi) has been shown to be an effective method of cancer therapy (12).…”
Section: Introductionmentioning
confidence: 99%